Hyaluronidase-responsive hydrogel loaded with magnetic nanoparticles combined with external magnetic stimulation for spinal cord injury repair - Zhiyi Fan; Guofu Zhang; Wanda Zhan; Juehan Wang; Chaoyong Wang; QianYing Yue; Zhangheng Huang; Yongxiang Wang (Materials Today Bio)
Spinal cord injury (SCI) is a neurological condition that causes significant loss of sensory, motor, and autonomic functions below the level of injury. Current clinical treatment strategies often fail to meet expectations. Hyaluronidase is typically associated with tumor progression and bacterial infections. Analysis showed that hyaluronidase also persistently increased in a rat total excision model. In this study, we designed a highly biocompatible dual-responsive hydrogel. Hyaluronic acid (HA)-Gelatin (Gel) served as the base for the hydrogel, crosslinked via an amide reaction to form the hydrogel. The hydrogel was further combined with Neurotrophic growth factor (NGF) and Fe3O4 nanoparticles, exhibiting low toxicity, good mechanical properties, self-healing ability, and sustained drug release. In cellular experiments, the novel hydrogel significantly promoted neural axon growth and development under an external magnetic field. Therapeutic results were confirmed in a rat spinal cord resection model, where inflammation was reduced, chondroitin sulfate proteoglycans decreased and a favorable environment for nerve regeneration was provided; neural regeneration improved hind limb motor function in SCI rats. These results underscore the therapeutic potential of hydrogel.